Reduction of Residual Stresses in Cold Expanded Thick-Walled Cylinders Using Plastic Stretching; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Bosnak A. O. Aleksey (2018, 2018)
Title screen